Pembentukan Karakter Anak Usia Dini melalui Gerakan Tujuh Kebiasaan Anak Indonesia Hebat - Sari, Muthia; Suliah, Suliah; Monalisa, Sofia; Rokhiyawati, Lilis; Oktanurina, Indah; Sotyaningsih, Dyah; Permatasari, Nenden; Nurhawiyah, Siti; Yusvinah, Yusvinah; Ghaisani, Syifa; Trikomalawati, Lili; Kartika, Neng (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Character building should be done from an early age. The Seven Habits of Great Indonesian Children movement launched by the government is a good practice to support character education, including character education in early childhood. The purpose of this socialization activity is to increase kindergarten teachers' understanding of the importance of children's character education and the consistency of kindergarten teachers to support the early childhood character building learning program in Cipocok District, Serang City. The research method used a participatory qualitative approach through interactive socialization, simulation, presentation, and focus group discussion. The main focus was the implementation of character education through the Seven Habits of Great Indonesian Children program. The results of the activity showed the high enthusiasm of kindergarten teachers to implement the Seven Habits of Great Indonesian Children program. Kindergarten teachers are also optimistic that the generation of Indonesian children will be better with the commitment and consistency between the government, schools, and parents, in implementing quality and sustainable education and care programs.